Hawaiian Gardens family portrait
Seven members of the Albanese/Talesfore/McArthur family at the Hawaiian Gardens. Standing from left to right: Ted Albanese, Dr. Charles "Bubber" McArthur, and Tony Talesfore. Seated from left to right: Georgia McArthur, Marian Talesfore, Margie Black Talesfore, and Christine "Tiny" Albanese McArthur. .